Detection of TP53 gene mutation in blood of breast cancer patients based on circulating tumor DNA and its application in prognosis: TP53 mutation in breast cancer prognosis - Lu, Qiran; Wei, Luxin; Cai, Shenbin; Zhang, Zhe; Zhang, Lifeng (Cellular and Molecular Biology, 2023)
This experiment was carried out to explore the application value of high throughput gene sequencing technology in detecting TP53 gene mutations in the blood of patients with breast cancer by detecting ctDNA gene mutations, and exploring the relationship between TP53 mutations and clinicopathological characteristics and prognosis of patients. The gene mutation of peripheral blood ctDNA and tissue paraffin DNA (tDNA) of 50 patients was detected by high-throughput sequencing technology. The basic data of 50 cases of Medium to high-risk breast cancer diagnosed and were retrospectively collected, and the clinicopathological characteristics and survival results of TP53 mutant and wild-type patients were compared and analyzed according to the ctDNA detection results and relevant follow-up data. Analyze the impact of TP53 mutations on overall survival and progression-free survival using univariate and multivariate Cox regression models. Among 50 patients, there were 29 cases of 7 kinds of gene mutations detected by ctDNA, and 37 cases of 9 kinds of gene mutations detected by tDNA. Using the gene mutation results detected by tDNA as the gold standard, the sensitivity and specificity of peripheral blood ctDNA in diagnosing TP53 gene mutations are 75% to 100%, 92.31% to 100%, and the overall coincidence rate with tDNA results was 83.33% to 100%. Exon 5 was the most prone to mutation, with a frequency of 24.14% (7/29). The most common type of mutation was the missense mutation of 37.93% (11/29). There was no significant correlation between TP53 mutation and PFS (HR=0.67, 95% CI: 0.41-1.08, P=0.102), while TP53 mutation was a protective factor for OS (HR=0.49, 95% CI: 0.27-0.90, P=0.022). The detection of ctDNA in peripheral blood of breast cancer patients by high-throughput gene sequencing technology can replace tumor tissue sections to understand gene mutation. The TP53 mutation in breast cancer patients is related to tumor size, lymph node metastasis and vascular tumor thrombus, but the prognosis of TP53 mutant patients is similar to that of wild-type patients.